The Degradation of Law and Democracy in Indonesia - Gunawan, Muhammad Safaat; Mujahidah, Nurul (International Journal of Law Society Services, 2024)
Executive dominance in Indonesia has long been a major concern in the administration of a democratic state. This has raised concerns about the potential disruption of power balance between the executive, legislative and judiciary, which are the main pillars in maintaining law and democracy. This article examined efforts to strengthen the checks and balances mechanism of the legislative and judiciary as a response to executive dominance. The research used a descriptive-analytical approach to explore how the role of the legislative and judiciary in controlling and balancing executive power. The results showed that despite the major challenges faced, there are significant efforts to strengthen the checks and balances mechanism, such as increasing the role of the DPR in oversight and legislation. In addition, maintain the independence of the judiciary in enforcing the law as well as the urgency of establishing a presidential law that can serve as a legal basis for the judiciary in taking action against various kinds of violations committed by state officials. Nonetheless, existing challenges exhibit the need for further reforms to ensure a healthy and sustainable balance of power, which is an essential prerequisite for maintaining the integrity of law and democracy in Indonesia.